DEVELOPMENT OF PROCESS KINETICS MODEL, HYDRODYNAMICS OF DISSOLVED AIR FLOTATION UNIT, AND CONCEPT OF MICRO-BUBBLE GENERATOR - BUDIANTO , HERY
Dissolved air flotation (DAF) is an unit operation applied for removal of solid phase from liquid phase or liquid phase from liquid phase. DAF utilizes micro air bubble for its exclusion. Exclusion process that occurred in DAF unit given by DAF kinetics. This dissertation successfully developed DAF kinetic model with based on two-way coupling method developed by Wang et al. (1998). Result of validation and calibration showed that model which have been developed are suitable to be applicated for the removal of tapioca particle from water. Advances CFD (Computational Fluid Dynamics) simulation of hydrodynamics was applied to analyze the hydrodynamics that occurred in DAF unit. Simulation of CFD that have been done is hydrodynamics at three dimensional (3D) flow and three phases. Primary phase is water as carrier phase, solid phase is tapioca particles and gas phase is bubble. Simulation conducted with various height of baffle in the DAF tank with its variation in 12,5; 32,5; 40,0; 60,0 cm and without baffle. CFD also linked to kinetic model developed to calculate the removal of tapioca particles with used velocity and pressure in each point of evaluation in flotation tank. This dissertation also developed the design concept of micro bubble generator for substitution of the pressure tank to increased the performance of DAF unit and reduced the operational cost of DAF unit.